2.5q-4.8-4.6q=-3.1q-2.7

Simple and best practice solution for 2.5q-4.8-4.6q=-3.1q-2.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.5q-4.8-4.6q=-3.1q-2.7 equation:


Simplifying
2.5q + -4.8 + -4.6q = -3.1q + -2.7

Reorder the terms:
-4.8 + 2.5q + -4.6q = -3.1q + -2.7

Combine like terms: 2.5q + -4.6q = -2.1q
-4.8 + -2.1q = -3.1q + -2.7

Reorder the terms:
-4.8 + -2.1q = -2.7 + -3.1q

Solving
-4.8 + -2.1q = -2.7 + -3.1q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '3.1q' to each side of the equation.
-4.8 + -2.1q + 3.1q = -2.7 + -3.1q + 3.1q

Combine like terms: -2.1q + 3.1q = 1q
-4.8 + 1q = -2.7 + -3.1q + 3.1q

Combine like terms: -3.1q + 3.1q = 0.0
-4.8 + 1q = -2.7 + 0.0
-4.8 + 1q = -2.7

Add '4.8' to each side of the equation.
-4.8 + 4.8 + 1q = -2.7 + 4.8

Combine like terms: -4.8 + 4.8 = 0.0
0.0 + 1q = -2.7 + 4.8
1q = -2.7 + 4.8

Combine like terms: -2.7 + 4.8 = 2.1
1q = 2.1

Divide each side by '1'.
q = 2.1

Simplifying
q = 2.1

See similar equations:

| X+(2A)+(B+2ft)=70 | | 5x+15=9-5(4x+4) | | 2.5q-4.8-4.6q=3.1q-2.7 | | y^4+6y-256=0 | | 34+10x=20+12x | | 4.9q-2.8-4.5q=0.6q-3.4 | | 3(2x+5)-15=4x+3.2-8x | | -2[5x]=18 | | -13=3x-4 | | 4x-9=12-3x | | -17+-2x=6-x | | 3[w]+15=9 | | 2[x]+7=21 | | 4h+10=6h+2 | | 4.9q-2.8-4.5q=-0.6q-3.4 | | 15x+26=236 | | [5-2y]+3=8 | | x^3-7x^2-168x+720=0 | | [2w+1]-3=2 | | y-1=.25 | | -.875-(-n)=-.58 | | 5x^2=-16x-3 | | 7.5y-0.5y=3.75y+39 | | 4-3(2a-1)=6a+1 | | 6+3x=12-x | | Y+.8=.75 | | Y=0.25x^3 | | 2[w-(2w+12)+7]=2(w+5) | | 60-6x=90-26x | | 7.5+0.5x=3x+1.5 | | 28=(16)-(4x) | | 3x(20-x)= |

Equations solver categories